Taxonomic Revision of the Leafhopper Genus Macropsis Lewis from Korea (Homoptera: Cicadellidae) - Kwon, Jin Hyung; Suh, Sang Jae; Kwon, Yong Jung (Zootaxa, 2021)
Korean species of the genus Macropsis Lewis are revised taxonomically, primarily based on the abdominal apodemes, male genitalia, and 2nd valvulae of the female ovipositor. Previously only three species were erroneously recorded from Korea. Among them, Macropsis notata (Prohaska, 1923) was previously misidentified as Macropsis prasina (Boheman, 1852). Two other European species, Macropsis scutellata (Boheman, 1845) and Macropsis illota (Horváth, 1899), are removed from the list of Korean fauna based on the examination of previously identified specimens that revealed only superficial resemblance to allied species. As a result, a total of 7 species are recognized in this revision, including 2 species new to science. Descriptions and distributional data are provided for all the species. Illustrations of both male and female genitalic characters as well as apodeme structures are provided, and an identification key to species from Korea is also given.